Realizing Islam: the Tijāniyya in North Africa and the eighteenth-century Muslim world - Wright, Zachary Valentine (Islamic civilization and Muslim networks, 2020)
"The Tijaniyya is the largest Sufi order in West and North Africa. In this unprecedented analysis of the Tijaniyya's origins and development in the late eighteenth century, Zachary Valentine Wright situates the order within the broader intellectual history of Islam in the early modern period. While introducing the group's founder, Ahmad al-Tijani (1735-1815), Wright's focus is on the wider network in which the order developed-a veritable global Islamic revival whose scholars commanded large followings, shared key ideas, and produced literature read widely throughout the Muslim world. They were linked, Wright shows, through chains of knowledge transmission in the face of widespread Muslim prejudice against Sufism"--